Prediction of Feeding Performance in Preterm Infants - Pickler, Rita H. (2005)
A nonexperimental study with a sample of 95 preterm infants was used to develop a model of feeding performance outcomes (proficiency, percent of prescribed volume consumed, and efficiency) using feeding readiness indicators (morbidity, maturity, behavior state at feeding start, and feeding experience). All readiness indicators were related to each other. In particular, there was a strong relationship between maturity and feeding experience. Morbidity only had an effect on efficiency; the most ill infants were less efficient feeders. Behavior state affects all feeding outcomes in a linear fashion; more awake and alert infants had better feeding performance outcomes. The effect of experience and maturity on the outcomes is more complex because of the relationship between the two. Experience has a greater effect as the infant matures, and as the infant matures, the amount of experience increases. Successful feeding requires maturity as well as experience.